High temperature wear micromechanisms in Al–17Si–5Cu alloy after an isothermal heat treatment. (3rd July 2021) - Hazra, Biplab; Bera, Supriya; Show, Bijay Kumar
ABSTRACT: The present investigation deals with the wear micromechanisms in hypereutectic Al–Si alloy containing Cu (AR alloy) after an isothermal heat treatment developed by the present authors. The heat-treated alloy (HT alloy) is subjected to a dry sliding wear test in a rotary tribometer under various loads against a hardened steel disk. Tests are conducted at higher temperatures, viz., at 200°C and 300°C. Worn surfaces and wear debris are characterised in the scanning electron microscope and X-ray diffractometer to find out wear mechanisms. The study reveals that severe wear occurs in the case of AR alloy at higher temperatures due to accelerated wear processes. On the other hand, HT alloy exhibits less wear due to resistance to wear in HT alloy. This improvement in wear behaviour in HT alloy is explained by the micromechanisms of wear.